Numerical investigations on the effect of blade tip winglet on leakage flow loss reduction for a zero inlet swirl turbine rotor. (11th August 2022) - Zhou, Qinghui; Zhao, Wei; Zhao, Qingjun; Sui, Xiuming; Xu, Jianzhong
Abstract: The tip leakage flow generates a large amount of aerodynamic losses in a zero inlet swirl turbine rotor (ZISTR), which directly uses the axial exit flow downstream of a combustion chamber without any nozzles. To reduce the tip leakage flow loss and improve the efficiency for the ZISTR, a front suction side winglet is employed on the blade tip, and the effect of winglet width is numerically investigated to explore its design space. It is found that, a suction side leading edge horseshoe vortex (SHV) on the blade tip plays a crucial role in mitigating the tip leakage flow loss. This SHV rotates in the reverse direction to the leakage vortex, so it tends to break the formation of the leakage vortex near the front part of suction side. With a larger winglet width, the SHV stays longer time on the blade tip and leaves it at a further downstream location. This increases the time and the contact area of the interaction between the SHV and the leakage vortex, so the leakage vortex is further weakened. Thus, the tip leakage flow loss is reduced, and the efficiency is improved. However, a larger winglet width also increases the heat load of the blade due to a larger blade surface area. The ZISTR designed with the winglet width equal to 2.1% blade pitch achieves a great trade-off between efficiency and heat load that the efficiency is improved by 0.85% at an expense of 1.2% increment of the heat load. Besides, for the blade using this winglet, the mechanical stress due to the centrifugal, aerodynamic and thermal load is acceptable for the engine application. This investigation indicates a great potential in the improvement of efficiency for the ZISTR using a blade tip winglet designed on the front suction side.